Early Attachment and the Development of Social Communication: A Neuropsychological Approach - Jethava, Vibhuti; Kadish, Jocelyn; Kakonge, Lisa; Wiseman-Hakes, Catherine (Frontiers in Psychiatry, 2022)
Social communication forms the foundation of human relationships. Social communication, i.e., the appropriate understanding and use of verbal and non-verbal communication within a social context, profoundly impacts mental health across the lifespan and is also highly vulnerable to neurodevelopmental threats and social adversities. There exists a strong interconnection between the development of language and other higher cognitive skills, mediated, in part, through the early attachment relationship. Consideration of how attachment links to brain development can help us understand individuals with social communication difficulties across the lifespan. The early attachment relationship supports the development of the foundational constructs of social communication. In this paper, a neuropsychological perspective was applied to social communication, which integrated evidence from early attachment theory, examining the underpinnings of social communication components identified by the SoCom model, namely socio-cognitive, socio-emotional, and socio-linguistic constructs. A neuropsychological perspective underscores the importance of interdisciplinary collaboration. This should also inform approaches to prevention, policy, intervention, and advocacy for individuals with or at risk for social communication impairments, as well as their families.